Effectivity of Entomopathogen of Fungi of Metarhizium brunneum Petch As Biotermitiside for Termite Pest of Coptotermes curvignathus Holmgren on Nutmeg in Aceh Province - Muhammad Sayuthi; Teguh Santoso; Iswadi Iswadi (The Faculty of Veterinary Medicine of Syiah Kuala University, 2018)
Abstract